2010
DOI: 10.1182/blood-2009-08-238626
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant roles for Runx1 alternative promoters reflect their activity at discrete stages of developmental hematopoiesis

Abstract: The transcription factor Runx1 is a pivotal regulator of definitive hematopoiesis in mouse ontogeny. Vertebrate Runx1 is transcribed from 2 promoters, the distal P1 and proximal P2, which provide a paradigm of the complex transcriptional and translational control of Runx1 function. However, very little is known about the biologic relevance of alternative Runx1 promoter usage in definitive hematopoietic cell emergence. Here we report that both promoters are active at the very onset of definitive hematopoiesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 51 publications
3
91
0
1
Order By: Relevance
“…Combination of VECadh or CD31 with the hematopoietic markers CD41 [40][41][42][43], CD45 [44] and Ter119 [45] has been used to separate endothelial from hematopoietic cells (e.g. [38,[46][47][48]), and other identification strategies have also been employed e.g. [49] [50].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
See 2 more Smart Citations
“…Combination of VECadh or CD31 with the hematopoietic markers CD41 [40][41][42][43], CD45 [44] and Ter119 [45] has been used to separate endothelial from hematopoietic cells (e.g. [38,[46][47][48]), and other identification strategies have also been employed e.g. [49] [50].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…This enhancer mediates reporter gene expression specifically to sites of HSPC emergence and colonization, but not to other areas of Runx1 expression later in development. In enhancerreporter transgenic mice, hematopoietic cells are marked throughout development [48,58]. In addition, we recently showed that this +23 enhancer-reporter transgene marks all hemogenic endothelium in the embryo, thus providing us with a unique marker to isolate hemogenic endothelium for detailed functional and molecular studies.…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…r gene (the Runx1 P1N allele) (26). Although NKT cell development was almost abolished in the Runx1 P1N/P1N mice, as reflected in the conditional inactivation of the Runx1 gene in CD4 + CD8 + double-positive thymocytes (21), other phenotypes, such as thymic hypocellularity, CD4 derepression in doublenegative thymocytes, and the reduction of CD4 + T cell numbers, were milder than those caused by inactivation of Runx1 gene (Supplemental Fig.…”
Section: P1-runx1 With the Neomentioning
confidence: 99%
“…In , and Runx1 PIN/P1N mice have been described previously (15,18,26). The generation of Cbfb 2m/2m mice by homologous recombination in embryonic stem cells will be described elsewhere.…”
mentioning
confidence: 99%